Variability in the development of synkinesis in a rabbit facial nerve axotomy model. Issue 7 (July 2021) - Wong, Manzhi; Takushima, Akihiko
Summary: Objective: Weakness and synkinesis (involuntary cocontraction of different muscle groups) are common sequelae after facial nerve injury. We describe a rabbit model of facial nerve axotomy and repair, which can be used to study such sequelae and propose a grading tool to assess the facial movement outcomes. Using this rabbit model, we assess the effect of delaying facial nerve repair on the quality of the clinical result. Methods: A total of 15 rabbits (30 facial halves) were divided into 4 groups: control, facial nerve main trunk axotomy and immediate repair, axotomy and repair at 2.5 weeks as well as axotomy, and repair at 2 months. Functional recovery was graded according to the observable criteria. We performed retrograde fluorescence labelling of the distal facial nerve branches and assessed the distribution of tracers in the facial nucleus. Results: A consistent model of weakness and synkinesis was produced in all rabbits after immediate axotomy and repair. A grading tool was used to clinically grade the quality of the recovery. The somatotopy of the facial nucleus was disrupted, with axons projecting from the facial nucleus to incorrect facial muscle groups. Varying the denervation time before repair affected the quality of the recovery. The worst result was noted when repair was delayed for 2 months. Subtle changes in the pattern and severity of synkinesis was noted among the different treatment groups. Conclusion: A slight delay in nerve repair by 2.5 weeks as well as contralateral facial paralysis (analogous to botulinum toxin (BTX) injection) appear to improve eye recovery and reduce synkinesis. Because of the large size of the rabbit, such variability in synkinesis severity can be graded.